The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4172/2315-7844.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality the Road Ahead for Student's Satisfaction

Abstract: The basic purpose of the current study was to investigate the relationship between service quality and student's satisfaction using HEdPERF model. The present study selected 384 respondents from 28 universities of Khyber Pakhunkhwa (Pakistan) using proportionate stratified random sampling method. The data was analysed with the help of SPSS and AMOS to measure service quality and student's satisfaction in higher education industry. The Factor Analysis and Parallel Analysis were also applied for purification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
5
8
1
Order By: Relevance
“…As as result of the literature review, it is seen that the number of studies using HEdPERF scale is increasing day by day (Ali, Shariff, Said & Mat, 2018;Ali et al, 2016;Ada, Baysal & Erkan, 2017;Banahene, Kraa & Kasu, 2018;Damaris, Surip & Setyadi, 2019;Deveci & Aymankuy, 2017;Firdaus, 2006;Firdaus, 2019;Khalid, Ali & Makhbul, 2019;Lazibat et al, 2014;Mang'unyi & Govender, 2014;Mekic & Mekic, 2016;Muhammad, Kakakhel, Baloch & Ali, (TKA, 2010: 5-73;TKA, 2013: 19-89). This study is intended to identify how tourism students at these three aforementioned universities view the service quality of institutions of higher education.…”
Section: Methodsmentioning
confidence: 99%
“…As as result of the literature review, it is seen that the number of studies using HEdPERF scale is increasing day by day (Ali, Shariff, Said & Mat, 2018;Ali et al, 2016;Ada, Baysal & Erkan, 2017;Banahene, Kraa & Kasu, 2018;Damaris, Surip & Setyadi, 2019;Deveci & Aymankuy, 2017;Firdaus, 2006;Firdaus, 2019;Khalid, Ali & Makhbul, 2019;Lazibat et al, 2014;Mang'unyi & Govender, 2014;Mekic & Mekic, 2016;Muhammad, Kakakhel, Baloch & Ali, (TKA, 2010: 5-73;TKA, 2013: 19-89). This study is intended to identify how tourism students at these three aforementioned universities view the service quality of institutions of higher education.…”
Section: Methodsmentioning
confidence: 99%
“…Reinforcing these findings, another study stated….. SQ (service quality) is a vital factor that determines the level of SS (student satisfaction)… (Wei, 2011), that good service quality will result in happy customers and costumers' repeat order for the previous services (Prentice & Kadan, 2019). Good service quality makes consumers feel more attached to the services provided (Kumar et al, 2018), and therefore, it is certain that students will be satisfied with the quality of service (Muhammad, Kakakhel, Baloch, & Ali, 2018b). Therefore, higher education managers should continuously examine their ability to provide quality services to students from various quality service dimensions (Onditi & Wechuli, 2017).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Furthermore, student satisfaction is determined by various aspects such as: academic aspects, non-academic aspects, access aspects, or communication aspects, problem solving aspects in the study program and the institution's reputation aspects. (Muhammad et al, 2018b). Non-academic aspects relate to the ability of the academic staff to assist and serve the needs of students: Academic aspects refer to the ability of the academic staff to convey the best knowledge and experience to students: Dimension access refers to the availability to be in contact with and to be approached by students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that service quality, particularly the dimensions of academic aspects, reputation, and program issues, impacted students' satisfaction. Finally, Muhammad et al (2018) investigated the effect of service quality on students' satisfaction for 384 students from 28 universities in Pakistan. They found that service quality, especially the dimensions of academic aspects, nonacademic aspects, reputation and access, were significant predictors of students' satisfaction.…”
Section: Students' Satisfaction In Hementioning
confidence: 99%